Cloning, Expression and Characterization of UDP-Glucose Dehydrogenases - Márcia R. Couto (MDPI AG, 2021)
Uridine diphosphate-glucose dehydrogenase (UGD) is an enzyme that produces uridine diphosphate-glucuronic acid (UDP-GlcA), which is an intermediate in glycosaminoglycans (GAGs) production pathways. GAGs are generally extracted from animal tissues. Efforts to produce GAGs in a safer way have been conducted by constructing artificial biosynthetic pathways in heterologous microbial hosts. This work characterizes novel enzymes with potential for UDP-GlcA biotechnological production. The UGD enzymes from Zymomonas mobilis (ZmUGD) and from Lactobacillus johnsonii (LbjUGD) were expressed in Escherichia coli. These two enzymes and an additional eukaryotic one from Capra hircus (ChUGD) were also expressed in Saccharomyces cerevisiae strains. The three enzymes herein studied represent different UGD phylogenetic groups. The UGD activity was evaluated through UDP-GlcA quantification in vivo and after in vitro reactions. Engineered E. coli strains expressing ZmUGD and LbjUGD were able to produce in vivo 28.4 µM and 14.9 µM UDP-GlcA, respectively. Using S. cerevisiae as the expression host, the highest in vivo UDP-GlcA production was obtained for the strain CEN.PK2-1C expressing ZmUGD (17.9 µM) or ChUGD (14.6 µM). Regarding the in vitro assays, under the optimal conditions, E. coli cell extract containing LbjUGD was able to produce about 1800 µM, while ZmUGD produced 407 µM UDP-GlcA, after 1 h of reaction. Using engineered yeasts, the in vitro production of UDP-GlcA reached a maximum of 533 µM using S. cerevisiae CEN.PK2-1C_pSP-GM_LbjUGD cell extract. The UGD enzymes were active in both prokaryotic and eukaryotic hosts, therefore the genes and expression chassis herein used can be valuable alternatives for further industrial applications.